THE FACE OF MALAY CULTURE IN INDONESIAN CHILDREN’S READINGS - Ratna Djumala (Hasanuddin University, 2018)
Awareness of national and cultural identity has nowadays become an increasingly popular topic of conversation. As the oldest culture in Indonesia, it is not surprising that Malay cultural values have embodied all aspects of Indonesian nationhood. Such values have been inveterately introduced to the people since their early age. Different media can be utilized to make this effort, one of which is children's readings. Despite the importance of introducing Malay culture to Indonesian society, however, not many children’s reading seemingly contains the virtues of Malay culture. As the result, children seem to have lack of knowledge and awareness of their culture of origin. While preliminary studies show that Malay cultural values can be found in Indonesian folklores, many Indonesian children are ironically not familiar with such folklores and instead more familiar with Malaysia-made animated shows such as Upin & Ipin and Pada Zaman Dahulu. With the strong influence of Malay culture in these two shows, it is understandable that Indonesian children learn more about Malay cultures from the shows. This paper aims to describe how Indonesian children recognize and learn about Malay culture from their readings, namely Upin & Ipin and Pada Zaman Dahulu. By observing this process, it is possible to identify any possible challenges to the cultural revitalization attempt, particularly of Malay culture, in Indonesian children's readings. This paper employs a descriptive and qualitative approach, using two Malaysia-made animations namely Upin & Ipin and Pada Zaman Dahulu as its object of research.